(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Physical vapor deposition (PVD) methods have attracted more attention through recent years. PVD methods have applied in various fields such as electronic devices, optical coatings, biomedical implants, aerospace applications and decorative parts. The principle of PVD method is depositing a thin film by intensifying material from the target on the substrate in vacuum or inert gas. This article reviews PVD methods with respect to principles, types, characteristics, and field of application. Three methods of PVD, such as thermal evaporation, sputtering, and pulsed laser deposition will be demonstrated with details.